KEMAMPUAN MENULIS PARAGRAF PERSUASI SISWA KELAS X SMA NEGERI 16 PADANG DENGAN MENGGUNAKAN MEDIA POSTER - Zamzuardi, Yosi; Asmawati, Asmawati; Muhardis, Muhardis (Pendidikan Bahasa Indonesia, 2013)
The problems that will be tell in this research is the students ability in writing Â persuasive paragraphs by using poster at class X in SMA Negeri 16 Padang. Based on the problems above, the purpose of this research is to know the students wryiting ability about persuasive paragraphs by using poster at class X in SMA Negeri 16 Padang.This kind of this research is quantitative research by using descriptive methods. The data were collected by using writing test persuasive paragraphs. The data analyzed consist of five levels based on a scale of 10. The population in this research was all of this students of class X SMA Negeri 16 Padang 2012-2013 year. The total of the population was 288, and the sample of this research was 36 people.After analysis, the research found that the student writing ability in write persuasive paragraphs by using media poster was as follows. First, based on the in indicators of the sentence contains an invitation, the qualification of the students was good with an value of 83,88 %. Second, based on the data indicator data and the fact, the qualification of the student was good with an value of 81.1 %. Third based on the this opinion indicators, the student the qualification of the student was good with an value of 92 %.